Transformasi Digital Layanan Internal melalui Aplikasi Helpdesk Ticketing Berbasis Web di PT Centrepark Citra Corpora - Cahyadi, Robby; Ramayanti, Desi (Prodi Teknik Informatika Universitas Pasir Pengaraian, 2025)
This study aims to design and develop a web-based helpdesk ticketing application to address the manual service management problems at PT Centrepark Citra Corpora. The method used is Rapid Application Development (RAD), which allows for rapid and iterative system development based on user feedback. The resulting system is a web-based helpdesk application featuring role-based login, ticket management, technician reporting, status notifications, and report generation. System design was based on user requirements analysis, visualized through a use case diagram and implemented within an integrated database structure. The system was tested using black-box testing and involved 10 internal users across three main roles (admin, technician, and client). Test results indicated that all features functioned as expected and were well received by users. The application has proven to improve efficiency, traceability, and documentation of internal technical services. This system is expected to support digital transformation initiatives and can be replicated in other organizations with similar service management needs.